Authorization Identification by Watermarking in Log-polar Coordinate System. (4th May 2018) - Yang, Zhi-Fang; Kuo, Chih-Ting; Kuo, Te-Hsi
Abstract: This study proposes a watermarking method for authorization identification which aims to prevent hackers from using copyrighted images without authorization. The watermark is embedded in the log-polar (LP) coordinate system which is resilient against rotation, scaling and translation (RST). For watermark detection, only the watermark is required at the receiver site, and whether the image is watermarked can be realized. The diffusion phenomenon of the embedded watermark is explored and used to make it possible to correlate the original watermark and the embedded watermark in the LPM domain. Experimental results show that the proposed scheme is robust against several attacks, such as rotation, rotation with cropping, scaling, scaling with cropping, translation, translation with cropping and JPEG compression.